Handbook of Pentecostal Christianity - Stewart, Adam (JSTOR EBA., 2012)
This is an easy-to-read guide designed for those interested in learning about one of the fastest-growing religious traditions in the world. Stewart's unique collection presents concise, yet comprehensive explanations of some of the most important terms and concepts needed to understand the origins and development of Pentecostalism worldwide.